2004
DOI: 10.5194/hess-8-334-2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for deep sub-surface flow routing in forested upland Wales: implications for contaminant transport and stream flow generation

Abstract: Upland streamflow generation has traditionally been modelled as a simple rainfall-runoff mechanism. However, recent hydrochemical studies conducted in upland Wales have highlighted the potentially important role of bedrock groundwater in streamflow generation processes. To investigate these processes, a detailed and novel field study was established in the riparian zone and lower hillslopes of the Hafren catchment at Plynlimon, mid-Wales. Results from this study showed groundwater near the river behaving in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 10 publications
4
94
2
Order By: Relevance
“…Responses in the intermediate piezometers showed similar variations for all three locations and trends were similar for the shallow and the intermediate piezometers. Haria and Shand (2004) showed that groundwater levels respond in a consistent way at different depths in the adjacent Hafren forested catchment and explained this in terms of a hydrostatic response to rapid recharge from rainfall upslope. It appears that a similar mechanism may be in operation within the moorland catchment.…”
Section: Temporal Changes In Groundwater Levelsmentioning
confidence: 88%
See 3 more Smart Citations
“…Responses in the intermediate piezometers showed similar variations for all three locations and trends were similar for the shallow and the intermediate piezometers. Haria and Shand (2004) showed that groundwater levels respond in a consistent way at different depths in the adjacent Hafren forested catchment and explained this in terms of a hydrostatic response to rapid recharge from rainfall upslope. It appears that a similar mechanism may be in operation within the moorland catchment.…”
Section: Temporal Changes In Groundwater Levelsmentioning
confidence: 88%
“…Observations in the adjacent Hafren forested catchment show that the response in piezometric heads to precipitation events is very rapid and implies rapid recharge via fracture and bypass flow Shand et al, 2004). Haria and Shand (2004) observed piezometers with artesian flow in the valley bottom and on the lower slopes indicating upward heads close to the river in the Hafren, a forested catchment of the river Severn. Given the fractured nature of the catchment and the steep topography a binary mixing model is proposed for the shallow groundwater system between recent recharge and older, deeper groundwaters.…”
Section: Soils and Vegetationmentioning
confidence: 91%
See 2 more Smart Citations
“…[5] Hydrometric [e.g., Haria and Shand, 2004] and hydrochemical [e.g., Mulholland, 1993;Burns et al, 1998;Katsuyama et al, 2005;Soulsby et al, 2007] evidence has suggested that groundwater that has infiltrated into bedrock discharges slowly into soil layers and contributes to base flow. Runoff of bedrock groundwater often strongly influences the generation of saturated zones in soil layers.…”
Section: Introductionmentioning
confidence: 99%